2016
DOI: 10.1097/cpm.0000000000000120
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Community-acquired Pneumonia in Adults: A Review

Abstract: The knowledge of risk factors for community-acquired pneumonia (CAP) is essential to the design of preventive measures to reduce its incidence. We present a review of the main risk factors for CAP in adults, paying particular attention to chronic comorbidities, medication, and lifestyle factors. The most frequently observed comorbidities associated with CAP are chronic obstructive pulmonary disease, asthma, and heart failure. Certain lifestyle factors such as smoking, dental hygiene, nutritional and dietary ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…15 Chronic lung disease, stroke, congestive heart failure, diabetes mellitus, immunosuppressive conditions, malnutrition were also reported as comorbidities influencing the presence of pneumonia in some studies. 13,15,16 Smoking an alcoholism was found to be an associated comorbidity in our study and this was corroborated by a study by Ramirez et al, where also they report smoking and overuse of alcohol to be a comorbidity. Torres et al and Almirall et al, in their respective studies also reported that smoking and over use of alcohol is associated with increased incidence of CAP.…”
Section: Discussionsupporting
confidence: 91%
“…15 Chronic lung disease, stroke, congestive heart failure, diabetes mellitus, immunosuppressive conditions, malnutrition were also reported as comorbidities influencing the presence of pneumonia in some studies. 13,15,16 Smoking an alcoholism was found to be an associated comorbidity in our study and this was corroborated by a study by Ramirez et al, where also they report smoking and overuse of alcohol to be a comorbidity. Torres et al and Almirall et al, in their respective studies also reported that smoking and over use of alcohol is associated with increased incidence of CAP.…”
Section: Discussionsupporting
confidence: 91%
“…Chronic conditions associated with pneumonia risk are well documented in advanced age categories [ 8 , 26 , 36 ]. We confirmed that asthma, diabetes, cardiovascular diseases and selected autoimmune conditions were also associated with pneumonia incidence in our young and working-age cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown an increasing trend both in mortality [20] and in morbidity due to PNM in the elderly in Brazil, even after the implementation of intervention strategies [22]. With advancing age, in addition to increasing exposure to environmental factors, the body's defense mechanisms reduce the ability to fight pathogenic microorganisms, increasing susceptibility to communicable diseases (immunosensitivity or immune aging), which is aggravated by the multicomorbidities present in this age group [6,7,[23][24][25]. Such an assertion may be associated with the increase in mortality rates in elderly people aged 80 years or older observed in this research.…”
Section: Discussionmentioning
confidence: 99%